PERAN PENGAWAS DALAM PENGEMBANGAN KEPROFESIAN BERKELANJUTAN BAGI GURU - Ika Berdiati (Tatar Pasundan : Jurnal Diklat Keagamaan, 2020)
The supervisor’s role is quite essential to support developing teacher competencies, and also to improve their professionalism. In this article, the author formulates the problem: what is the role of supervisors in continuing professionalism development for teachers?. The purpose of this article is to describe strategies executed by supervisor on carrying out the academic task related to improving teacher’s pedagogical and professional competence. The results appertained to their role of improving teacher’s competence both pedagogically and professionally can be accomplished through academic supervision competencies. Other observable strategies are developing scientific publication, creating learning tools or teaching aids (innovative works); modifying practicum and self-development tools came under education and training, and KKG.Keywords: Pedagogy; Professional; Scientific publication; Innovative works